Role of Cultural Resources in Mental Health: An Existential Perspective - Shukla, Shashwat (Frontiers in Psychology, 2022)
A reductionist view of mental health tends to give limited results. While some important benefits are still achieved, other key elements are left unaddressed. These gaps tend to wipe out the gains which were made by focusing on the dominant aspects of mental health that are promoted by a reductionist view. This paper explores such gaps by looking at those healing traditions which view health and wellness from a broader perspective. Through the live experience of such traditions the paper tries to illustrate how the deeper aspects of mental health are also relevant. The paper attempts to argue that diverse cultures have inbuilt repositories of existential wisdom which can help in promoting and maintaining positive mental health through a conceptual exploratory analysis.